HMGB1 and Histones Play a Significant Role in Inducing Systemic Inflammation and Multiple Organ Dysfunctions in Severe Acute Pancreatitis - Runkuan Yang; Jyrki Tenhunen; Tor Inge Tonnessen (Hindawi Limited, 2017)
Severe acute pancreatitis (SAP) starts as a local inflammation of pancreatic tissue that induces the development of multiple extrapancreatic organs dysfunction; however, the underlying mechanisms are still not clear. Ischemia-reperfusion, circulating inflammatory cytokines, and possible bile cytokines significantly contribute to gut mucosal injury and intestinal bacterial translocation (BT) during SAP. Circulating HMGB1 level is significantly increased in SAP patients and HMGB1 is an important factor that mediates (at least partly) gut BT during SAP. Gut BT plays a critical role in triggering/inducing systemic inflammation/sepsis in critical illness, and profound systemic inflammatory response syndrome (SIRS) can lead to multiple organ dysfunction syndrome (MODS) during SAP, and systemic inflammation with multiorgan dysfunction is the cause of death in experimental SAP. Therefore, HMGB1 is an important factor that links gut BT and systemic inflammation. Furthermore, HMGB1 significantly contributes to multiple organ injuries. The SAP patients also have significantly increased circulating histones and cell-free DNAs levels, which can reflect the disease severity and contribute to multiple organ injuries in SAP. Hepatic Kupffer cells (KCs) are the predominant source of circulating inflammatory cytokines in SAP, and new evidence indicates that hepatocyte is another important source of circulating HMGB1 in SAP; therefore, treating the liver injury is important in SAP.